Răspuns :
a)5√6+3√6=√6(5+3)=8√6
b)√10+2√10=√10(1+2)=3√10
c)3√2-5√2-8√2=√2(3-5-8)=-10√2
d)√7+√7+√7+√7=√7(1+1+1+1)=4√7 asta e ceea ce am inteles eu din subpunctul acesta...
e)-√5-√5-√5-√5=√5(-1-1-1-1)=-4√5
f)√12+√75=
√12=√(2²·3)=2√3
√75=√(5²·3)=5√3
2√3+5√3=√3(2+5)=7√3
b)√10+2√10=√10(1+2)=3√10
c)3√2-5√2-8√2=√2(3-5-8)=-10√2
d)√7+√7+√7+√7=√7(1+1+1+1)=4√7 asta e ceea ce am inteles eu din subpunctul acesta...
e)-√5-√5-√5-√5=√5(-1-1-1-1)=-4√5
f)√12+√75=
√12=√(2²·3)=2√3
√75=√(5²·3)=5√3
2√3+5√3=√3(2+5)=7√3
a) 5√6+3√6=8√6
b) √10+2√10=3√10
c)3√2-5√2-8√2 = - 10√2
d)√7+√7+√7+√7=4√7 (verifica daca este asa, caci enuntul este gresit)
e) -√5 -√5- √5- √5= -4√5
f)√12+√75=√4*3 +√25*3=2√3 +5√3=7√3
b) √10+2√10=3√10
c)3√2-5√2-8√2 = - 10√2
d)√7+√7+√7+√7=4√7 (verifica daca este asa, caci enuntul este gresit)
e) -√5 -√5- √5- √5= -4√5
f)√12+√75=√4*3 +√25*3=2√3 +5√3=7√3